Financial ratio analysis of a foreign bank in Bangladesh a detailed analysis of bank Alfalah - Shathi, Habiba Akter (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.